Small extracellular vesicles and their miRNA cargo are anti-apoptotic members of the senescence-associated secretory phenotype - Terlecki-Zaniewicz, Lucia; Scheideler, Marcel (Aging, 2018)
Loss of functionality during aging of cells and organisms is caused and accompanied by altered cell‐to‐cell communication and signalling. One factor thereby is the chronic accumulation of senescent cells and the concomitant senescence‐associated secretory phenotype (SASP) that contributes to microenvironment remodelling and a pro‐inflammatory status. While protein based SASP factors have been well characterized, little is known about small extracellular vesicles (sEVs) and their miRNA cargo. Therefore, we analysed secretion of sEVs from senescent human dermal fibroblasts and catalogued the therein contained miRNAs. We observed a four‐fold increase of sEVs, with a concomitant increase of >80% of all cargo miRNAs. The most abundantly secreted miRNAs were predicted to collectively target mRNAs of pro‐apoptotic proteins, and indeed, senescent cell derived sEVs exerted anti‐apoptotic activity. In addition, we identified senescencespecific differences in miRNA composition of sEVs, with an increase of miR‐23a‐5p and miR‐137 and a decrease of miR‐625‐3p, miR‐766‐3p, miR‐199b‐5p, miR‐381‐3p, miR‐17‐3p. By correlating intracellular and sEV‐miRNAs, we identified miRNAs selectively retained in senescent cells (miR‐21‐3p and miR‐17‐3p) or packaged specifically into senescent cell derived sEVs (miR‐15b‐5p and miR‐30a‐3p). Therefore, we suggest sEVs and their miRNA cargo to be novel, members of the SASP that are selectively secreted or retained in cellular senescence.
Gesehen am 14.05.2019